(untitled) (Scientific Conference on Multidisciplinary Studies, 2025)
This article provides an overview of interference in English language learning, emphasizing its types and strategies to address challenges faced by learners. The interference arising from the negative consequences of one language on another covers all linguistic levels ofthe language being studied, including the lexical one, which leads to deviations from the language norm and numerous lexical errors of students. The author of the article investigates the concept of linguacultural interference and indicates the types of interference. Understanding these concepts can lead to more effective language acquisition and teaching methods.